2020
DOI: 10.3983/twc.2020.1675
|View full text |Cite
|
Sign up to set email alerts
|

Fan geographies and engagement between geopolitics of Brexit, Donald Trump, and Doctor Who on social media

Abstract: The 2016 Brexit decision and Donald Trump's election to the US presidency that same year led to a wide variety of social media activity, ranging from visceral anger to unadulterated jubilation. How members of particular fandoms choose to express their emotions regarding a geopolitical event can be filtered through the lens of their fannish enthusiasm. Analysis of Doctor Who-influenced geopolitical engagement on Facebook that uses case studies of both Brexit and Donald Trump's election and 2017 inauguration sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For some time, fans have turned to the internet to find venues to interact with others interested in the same cultural objects (Baym, 1994;Fiesler & Dym, 2020). Like other social media spaces, subreddits serve as centers of community for fans of cultural products (Gunderman, 2020). Despite a history of research finding that fans create cultural meaning with the popular culture they consume (Fiesler et al, 2016;Jenkins, 1992), a contrasting conceptualization is that fans may be "ideal consumers [who] automatically buy the latest works" (Cavicchi, 1998, p. 62), and that fandom and consumerism are heavily intertwined (Hills, 2003;Stanfill, 2019).…”
mentioning
confidence: 99%
“…For some time, fans have turned to the internet to find venues to interact with others interested in the same cultural objects (Baym, 1994;Fiesler & Dym, 2020). Like other social media spaces, subreddits serve as centers of community for fans of cultural products (Gunderman, 2020). Despite a history of research finding that fans create cultural meaning with the popular culture they consume (Fiesler et al, 2016;Jenkins, 1992), a contrasting conceptualization is that fans may be "ideal consumers [who] automatically buy the latest works" (Cavicchi, 1998, p. 62), and that fandom and consumerism are heavily intertwined (Hills, 2003;Stanfill, 2019).…”
mentioning
confidence: 99%
“…In this paper, we intend to discuss these approximations between politics and pop culture in the Global South (Martino & Marques, 2022) from theoretical contributions that help to understand the phenomenon of Social TV in Brazil (Canatta, 2019) and even Fan Cultures (Author et al, 2021;Gunderman, 2020;Bennet, 2012 and others) that emerged around this set of profiles on Twitter. So, we conducted an exploratory research based on a Boolean search with some terms found on Twitter during CPI's exhibition.…”
Section: Fan Practices Around the "Cpi Da Covid": Intersections Betwe...mentioning
confidence: 99%
“…(In this paper we are using the term “post” in a generic way, for any posting to the site, whereas Reddit delineates between “submissions” which are new, top-level posts, and “comments” which are replies to both submissions and other comments.) It also allows us to examine spaces where fans of particular cultural products communicate with other fans (Gunderman, 2020), providing an opportunity to observe how conversations and communities shift and change over time. Subreddits related to older games remain active, sometimes over a decade after a game’s initial release.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fans of one game in a franchise might play and become a fan of a new release in that franchise, or they might not. Although fans utilize different online spaces (and those spaces have changed over time—see Fiesler et al [2016]), many fans currently use Reddit to be part of fan-based communities and to discuss the objects of their fandom with fellow fans (Gunderman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%